2019
DOI: 10.1088/1361-6668/ab1660
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundary characteristics of oxypnictide NdFeAs(O,F) superconductors

Abstract: We have systematically investigated the grain boundary angle (θ GB ) dependence of transport properties for NdFeAs(O,F) fabricated on [001]-tilt symmetric MgO bicrystal substrates. In our previous study, NdFeAs(O,F) bicrystal films showed a weak-link behaviour even at a θ GB of 6 • . However, this was caused by an extrinsic effect originating from the damage to both NdFeAs(O,F) and MgO substrate by excess F-diffusion along the grain boundary. To investigate the intrinsic nature of grain boundaries, we minimize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The film growth was monitored by reflection high-energy electron diffraction (RHEED). To obtain NdFeAs(O,F) films with different F content, a 20 nm-thick NdOF overlayer was deposited on top of the NdFeAsO layer at various temperatures in the range of 550 22 , where T dep is the deposition temperature. Since it is difficult to determine the fluorine content precisely, both the c-axis lattice parameter and T c have been used as the indicators of the F-content in Nd-FeAs(O,F).…”
Section: Methodsmentioning
confidence: 99%
“…The film growth was monitored by reflection high-energy electron diffraction (RHEED). To obtain NdFeAs(O,F) films with different F content, a 20 nm-thick NdOF overlayer was deposited on top of the NdFeAsO layer at various temperatures in the range of 550 22 , where T dep is the deposition temperature. Since it is difficult to determine the fluorine content precisely, both the c-axis lattice parameter and T c have been used as the indicators of the F-content in Nd-FeAs(O,F).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, these HAGBs become serious weak links. 5,6 In our previous study, 7 θ c was evaluated to be 8.5°for NdFeAs(O,F) bicrystals with symmetrical [001]-tilt boundaries, which is close to θ c ∼ 9°for Co-doped BaFe 2 As 2 (Ba-122) 8 and Fe(Se,Te) bicrystals. 9,10 Therefore, strict control of the texture is required to fully utilize its potential advantages in applications.…”
Section: Introductionmentioning
confidence: 53%
“…However, polycrystalline Ln FeAs­(O,F) generally does not show the best performance, because J c significantly decreases in the presence of high-angle grain boundaries (HAGB) with misorientation angles larger than the critical angle θ c , for which intergrain J c starts to decrease exponentially. Hence, these HAGBs become serious weak links. , In our previous study, θ c was evaluated to be 8.5° for NdFeAs­(O,F) bicrystals with symmetrical [001]-tilt boundaries, which is close to θ c ∼ 9° for Co-doped BaFe 2 As 2 (Ba-122) and Fe­(Se,Te) bicrystals. , Therefore, strict control of the texture is required to fully utilize its potential advantages in applications.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, the formation of Ba-O and Fe-Co-As enriched phases as the secondary phases in the aggregates was observed. Several previous studies have reported similar phases in Ba-122 bulks that were fabricated in a glove box [10,25]. Therefore, even at a low temperature of 600 °C, phase separation may have occurred owing to the loss of Ba atoms from the grain surface.…”
Section: Discussionmentioning
confidence: 81%
“…Iron-based superconductors also have inherently weak links [20][21][22]. Previous studies have shown that the transport critical current in Fe (Se,Te) decreases to approximately 1/5th-1/4th at a misorientation angle of 15° compared to that at 0° and further decreases by an order of magnitude at 25° [21][22][23][24][25]. In our previous study, we found a correlation between the improvement in critical current characteristics and the reduction in grain size by microstructural analysis using electron microscopy [26].…”
Section: Introductionmentioning
confidence: 99%